THE EFFECT OF BLENDED LEARNING ON STUDENT’S SELF EFFICACY IN MATHEMATIS LEARNING - Nadrah Afiati Nasution (Journal Mathematics Education Sigma [JMES], 2024)
This research aims to find out whether there is a significant influence from blended learning on students' self-efficacy in learning mathematics. This type of research is quantitative research. The instruments used are tests and questionnaires. The questionnaire distributed to the sample was tested for feasibility using validity and reliability tests. The data analysis technique in this research uses simple linear regression analysis, which aims to see the effect of blended learning on students' self-efficacy in learning mathematics. The research subjects were 95 students of SMK Sandhy Putra – 2 Medan, obtained through random sampling techniques and the Slovin method. The results of the research show that there is an influence of the blended learning model on students' self-efficacy in mathematics learning, with the influence of blended learning on students' self-efficacy of 65.8%.